Effect of Propofol on Acid Reflux Measured with the Bravo pH Monitoring System. (22nd April 2013) - Chawla, Anupama; Girda, Eugenia; Walker, Grace; Turcotte Benedict, Frances; Tempel, Mila; Morganstern, Jeffrey
Abstract : Background/Aim . The aim of this study was to determine the effect of propofol on acid reflux as measured with the Bravo pH monitoring system. Methods . 48-hour pH tracings of 88 children were retrospectively evaluated after placement of the Bravo capsule under propofol. Comparisons between day 1 and day 2, as well as 6-hour corresponding segments from day 1 and day 2, were made. Results . The number of reflux episodes was significantly increased during the first six-hour period on day one as compared to day 2 ( P = 0.006 ) . The fraction of time the pH was <4 was also increased during this period, though it did not reach statistical significance. When comparing full 24-hour periods, there was no difference noted in either the number of reflux episodes or the fraction of time pH < 4 between day one and day two. Conclusion . Our data suggest an increase in gastroesophageal reflux during the postanesthesia period. This could be a direct effect of propofol, or related to other factors. Regardless of the cause, monitoring of pH for the first 6 hours following propofol administration may not be reliable when assessing these patients. Monitoring pH over a prolonged 48-hour time period can overcome this obstacle.